2017
DOI: 10.1016/s1470-2045(17)30450-3
|View full text |Cite|
|
Sign up to set email alerts
|

Ipatasertib plus paclitaxel versus placebo plus paclitaxel as first-line therapy for metastatic triple-negative breast cancer (LOTUS): a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial

Abstract: Summary Background The oral AKT inhibitor ipatasertib is being investigated in cancers with a high prevalence of PI3K/AKT pathway activation, including triple-negative breast cancer. The LOTUS trial investigated the addition of ipatasertib to paclitaxel as first-line therapy for triple-negative breast cancer. Methods In this randomised, placebo-controlled, double-blind, phase 2 trial, women aged 18 years or older with measurable, inoperable, locally advanced or metastatic triple-negative breast cancer previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
346
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 411 publications
(364 citation statements)
references
References 31 publications
14
346
0
4
Order By: Relevance
“…In most breast cancer series this is the most frequently altered potentially actionable pathway, thus these alterations are actively being pursued in trials with PI3K/AKT/ mTOR inhibitors. 2,23,24 CDH1 mutations, as expected, were almost exclusively found in invasive lobular carcinoma. CDH1 loss is pathognomonic for lobular carcinomas; the fact that we found CDH1 mutations in only 56% of patients suggests that CDH1 loss may also be mediated through non-genomic mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…In most breast cancer series this is the most frequently altered potentially actionable pathway, thus these alterations are actively being pursued in trials with PI3K/AKT/ mTOR inhibitors. 2,23,24 CDH1 mutations, as expected, were almost exclusively found in invasive lobular carcinoma. CDH1 loss is pathognomonic for lobular carcinomas; the fact that we found CDH1 mutations in only 56% of patients suggests that CDH1 loss may also be mediated through non-genomic mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…The treatment arms of the screened 28 studies were recorded, yet Dieras’ study, which compared the efficacy between onartuzumab + bevacizumab + CT, bevacizumab + CT + placebo, and onartuzumab + CT + placebo for TNBC patients, was excluded because the treatments did not share common nodes with the others . Finally, 27 RCTs involving 6924 TNBC patients were included and the characteristics of the included trials are displayed in Table …”
Section: Resultsmentioning
confidence: 99%
“…A single-arm, phase 2 neoadjuvant clinical trial was conducted using the AKT inhibitor MK-2206 in combination with anastrozole in advanced breast cancer patients with a PIK3CA mutation. The LOTUS phase 2 clinical trial found that patients with TNBC treated with ipatasertib and paclitaxel had improved PFS compared with paclitaxel alone (6.2 vs 4.9 months), 63 providing the rationale for IPATunity130. 62 Furthermore, a patient in this study acquired an ESR1 mutation detected at the time of surgery.…”
Section: Ddpcr Detection Of Esr1 Mutations In Patient Biopsiesmentioning
confidence: 99%